2012
DOI: 10.1051/0004-6361/201117386
|View full text |Cite
|
Sign up to set email alerts
|

A fresh insight into the evolutionary status and third body hypothesis of the eclipsing binaries AD Andromedae, AL Camelopardalis, and V338 Herculis

Abstract: Aims. We aim to derive the absolute parameters of the components of AD And, AL Cam, and V338 Her, interpret their orbital period changes and discuss their evolutionary status. Methods. New and complete multi-filter light curves of the eclipsing binaries AD And, AL Cam, and V338 Her were obtained and analysed with modern methods. Using all reliably observed times of minimum light, we examined orbital period irregularities using the least squares method. In addition, we acquired new spectroscopic observations du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 41 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…It is necessary to note that the relative statistical error of Q is almost 90%, what degrades its significance. We have tried also solution with no Q and we surprisingly obtained results with worse Our solution imply minimal 3 rd body mass (for i 3 = 90 • ) of ∼ 2.33 M ⊙ , using absolute parameters from Liakos et al (2012). This would yield the third light about 15% to the total luminosity of the system.…”
Section: Ad Andmentioning
confidence: 81%
See 4 more Smart Citations
“…It is necessary to note that the relative statistical error of Q is almost 90%, what degrades its significance. We have tried also solution with no Q and we surprisingly obtained results with worse Our solution imply minimal 3 rd body mass (for i 3 = 90 • ) of ∼ 2.33 M ⊙ , using absolute parameters from Liakos et al (2012). This would yield the third light about 15% to the total luminosity of the system.…”
Section: Ad Andmentioning
confidence: 81%
“…Giuricin & Mardirossian (1981) published photometric parameters of the system and concluded that both components have almost the same radii, masses, temperatures and luminosities with orbital inclination i = 81.9 • ± 0.4 • , which was confirmed by Liakos et al (2012). The period variations of AD And were investigated by several authors (Walker 1957;Ruciński 1966;Frieboes-Conde & Herczeg 1973;Liao & Qian 2009;Liakos et al 2012). The last mentioned authors determined period of the third body to be 14.3 years and its mass function f (m) = 0.183 M ⊙ .…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations